Dynamic expiratory CT: An effective non‐invasive diagnostic exam for fragile children with suspected tracheo‐bronchomalacia. Issue 1 (17th November 2017) - Ullmann, Nicola; Secinaro, Aurelio; Menchini, Laura; Caggiano, Serena; Verrillo, Elisabetta; Santangelo, Teresa Pia; Cutrera, Renato; Tomà, Paolo
Abstract: Background: Tracheobronchomalacia, defined as variable collapse of the airways, has been recognized as an important cause of respiratory morbidity but still widely underdiagnosed. Bronchoscopy is still considered as the gold standard, but numerous limitations are known, especially for fragile sick children. Moreover, information on parenchymal lung disease cannot be described. There is a real need for a reliable, non‐invasive test to help detection of airway and parenchymal malformations in children, specifically when bronchoscopy cannot be performed. Methods and Results: 34 paediatric patients underwent cine multidector CT for ongoing respiratory symptoms and were included. All CT images were of good quality and sedation was never needed. Airway disease such as trachea‐broncomalacia with/without stenosis was described in 53% with the first being more frequent. Bronchomalacia alone was described in 10 patients and in 4 patients was associated with tracheomalacia. Moreover, CT allowed identification of parenchymal disease in 10 patients. Airways stenosis alone was detected in seven patients. The majority of patients (85%) underwent also bronchoscopy for clinical decision. The agreement between CT and bronchoscopy was explored. The two examinations did not agree only in two cases. CT dynamic showed an excellent sensitivity of 100% (81.47‐100 %), a great specificity of 82% (48.22‐97.72 %), NPV 100%, and PPV 90% (72‐96.9 %). Conclusion: Dynamic CT results an effective and highly sensitive diagnostic exam for children with tracheo‐bronchomalacia. CT is especially indicated for those small and fragile patients that cannot undergo an invasive investigation. Moreover, CT allows a detailed evaluation both of the airways and the lungs which is useful for the clinical management.